Mathematical proof of the first stage of the law of karma that good deeds lead to happiness and bad deeds lead to suffering. What is buddha-“God” by buddhist religion understanding? - Dorj, Jargal (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In this paper, we will prove the Buddhist teaching that good deeds/actionlead to happiness and bad deeds lead to suffering has a scientific verification by using an optimal control theory branch of mathematics.TheBuddhist teaching considers thatBuddha is a good mind/soul with information about good deeds or good karma. Here we will prove this view has scientific evidence as a theorem.